Pengaruh Intellectual Capital, Struktur Modal, Kepemilikan Institusional terhadap Kinerja Keuangan dengan Ukuran Perusahaan Sebagai Pemoderasi - Kusniawati, Heni; Nuryatno Amin, Muhammad (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The study aims to determine the effect of Intellectual Capital, Capital Structure and Institutional Ownership on Financial Performance with Company Size as Moderating in financial sector companies listed on the Indonesia Stock Exchange (BEI) Period 2020-2022. The research was conducted using a quantitative methods. The data used in this study were secondary data obtained from the financial statements and annual report of financial sector companies listed on the Indonesia Stock Exchange (BEI) Period 2020-2022. The sampling technique used was by purposive sampling with predetermined criteria resulting in 61 companies for 3 years and then the total sample of 174 data. The research analysis method is with multiple linear regression analysis and uses IBM SPSS to test and process this research data. The results of the research concluded that intellectual capital had a positive effect on financial performance, while capital structure and institutional ownership has no effect on financial performance. company size as a moderator is not able to strengthen the positive influence of intellectual capital and institutional ownership on financial performance. However, size of the company can weaken the influence of capital structure on financial performance.